2003
DOI: 10.1108/07363760310464613
|View full text |Cite
|
Sign up to set email alerts
|

Parental influence on the purchase of luxury brands of infant apparel: an exploratory study in Hong Kong

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 13 publications
2
89
2
1
Order By: Relevance
“…Furthermore, the purchase of such products may improve the status for people of all social classes (Cuneo, 1996). Generally, luxury items are high-involvement products that are purchased to gain status (Prendergast & Wong, 2003) and are related to conspicuous consumption (Wong, 1997). Opinion leaders influence the consumers' decision-making and are significant in disseminating information, specifically about high-involvement purchases .…”
Section: High-involvement Productsmentioning
confidence: 99%
“…Furthermore, the purchase of such products may improve the status for people of all social classes (Cuneo, 1996). Generally, luxury items are high-involvement products that are purchased to gain status (Prendergast & Wong, 2003) and are related to conspicuous consumption (Wong, 1997). Opinion leaders influence the consumers' decision-making and are significant in disseminating information, specifically about high-involvement purchases .…”
Section: High-involvement Productsmentioning
confidence: 99%
“…In fact, this perception is totally opposite with the old one in which only upper class people have the right for luxury goods. (Kapferer, 2012) When upmarket products are considered, according to Prendergast & Wong (2003), quality is a more important criteria than price. Luxury brands need to be aware that for upmarket consumers what matters is the quality not the price.…”
Section: The Concept Of Luxurymentioning
confidence: 99%
“…They reported that the popularity of a brand could propel the dream value of the brand. Prendergast and Wong (2003) considered the concepts of buying roles, conspicuous consumption/social consumption motivation, and materialism. They reported a poor relationship between the amount of money spent by parents on luxury brands of infant apparel and social consumption motivation.…”
Section: Introductionmentioning
confidence: 99%